Functional Disability Among Older Versus Younger Adults With Advanced Non–Small-Cell Lung Cancer. Issue 6 (June 2021) - Presley, Carolyn J.; Arrato, Nicole A.; Janse, Sarah; Shields, Peter G.; Carbone, David P.; Wong, Melisa L.; Han, Ling; Gill, Thomas M.; Allore, Heather G.; Andersen, Barbara L.
Abstract : PURPOSE: To determine patient and disease characteristics associated with functional disability among adults with advanced non–small-cell lung cancer (NSCLC). METHODS: In a prospective cohort of participants newly diagnosed with advanced NSCLC and beginning systemic treatment, functional disability in usual activities, mobility, and self-care was measured using the EuroQol-5D-5L at baseline. Demographics, comorbidities, brain metastases, Eastern Cooperative Oncology Group performance status (ECOG PS), and psychologic variables (depression [Patient Health Questionnaire-9] and anxiety [Generalized Anxiety Disorder 7-item scale]) were captured. Patients were classified into two disability groups (none-slight or moderate-severe) on the basis of total functional status scores. Differences between disability groups were determined (chi-square and t tests). Associations between patient characteristics and baseline disability were assessed using logistic regression. RESULTS: Among 173 participants, mean age was 63.3 years, 56% were male, 83% had ECOG PS 0-1, and 41% had brain metastases. Baseline disability was present in 39% of participants, with patients having moderate to severe disability in usual activities (37.6%), mobility (26.6%), and self-care (5.2%). Depressive and/or anxiety symptoms ranged from none to severe (Patient Health Questionnaire 9-item scale M = 6.5, SD = 5.3). Depressive symptoms were the only characteristic associated with a higher odds of baseline disability (adjusted odds ratio [aOR]: 1.26; 95% CI, 1.15 to 1.38; P < .001). Participants with poorer ECOG PS (aOR: 4.64; 95% CI, 1.84 to 11.68; P = .001) and depressive symptoms (aOR: 1.15; 95% CI, 1.07 to 1.24; P < .001) had higher odds of moderate-severe mobility disability compared with the none-slight disability group. CONCLUSION: More than one third of all adults with advanced NSCLC have moderate-severe functional disability at baseline. Psychologic symptoms were significantly associated with moderate-severe baseline disability.